Physiological and biochemical responses of selected cowpea (Vigna unguiculata (L.) Walp.) accessions to iron toxicity - Josiah ESEOGHENE IFIE; Sandra OMON IFIE-ETUMAH; Beckley IKHAJIAGBE (Acta Agriculturae Slovenica)
This study aimed to investigate the effect of iron toxicity in cowpea using physiological and biochemical responses of selected accessions. Fifteen accessions of cowpea were exposed to two treatments of iron using FeSO4 solution (100 mg l-1 and 400 mg l-1) and distilled water at pH 6.2 as control. The results showed that there was a general reduction in germination morphology; germination percentage among the 400 mg l-1 Fe-treated accessions. Seed mortality rates were significantly higher among the 400 mg l-1Fe-treated accessions (> 35 %). Water imbibition capacity and relative mass gained were higher for Fe-treated accessions. Furthermore, significant increase in the total sugar and percentage utilization of sugars was accompanied by an insignificant decrease in chlorophyll a, a significant decrease in chlorophyll b contents and the persistence of foliar chlorosis, among the 400 mg l-1 Fe-treated accessions. MDA levels were significantly increased while proline remained unchanged, mean SOD activity was insignificantly increased, whereas Cat decreased among the 400 mg l-1 Fe-treated accessions. Documentation of these observable changes in physiological and biochemical parameters will be useful in understanding the impact of elevated iron concentrations on the cultivation of cowpea accessions in soils associated with ferruginous ultisols.